PEMBELAJARAN BAHASA INDONESIA YANG BERKARAKTER, AKTIF, DAN MENYENANGKAN DI SD MUHAMMADIYAH 10 SURAKARTA - Fitri Puji Rahmawati; Utami Magrifiani; Malika Dian Ayu Noviati (Universitas Muhammadiyah Surakarta, 2014)
The aim of this study include: a) describe the character of learning Indonesian, active,and fun in SD Muhammadiyah Surakarta 1, b) describe a method of learning Indonesiancharacter, active, and fun in SD Muhammadiyah Surakarta 10, and c) describeobstacles encountered in the implementation of learning Indonesian character, active,and fun in SD Muhammadiyah Surakarta 10. This research is a qualitative descriptivestudy. The strategy used is a single case study. The main data source of this research:teacher and fourth grade students in 10 elementary Muhammadiyah Surakarta. Severaldata collection techniques: direct observation plays a passive, in-depth interviews,open and informal nature, giving questionnaires (open questionnaire). Implementationof learning character, active, and fun on Indonesian subjects in fourth grade SurakartaMuhammadiyah 10 can be observed from the three activities, namely: planning learning,learning implementation, and evaluation of learning. Learning plan has been availablesyllabi and lesson plans, instructional implementation has accordance RPP but lessvariable in the application of the method, and the evaluation of teacher learning hasdeveloped rubrics and assessment in the lesson plan format. Constraints faced to implementthe learning of character, active, and fun on Indonesian subjects in fourth gradeSurakarta Muhammadiyah 10, among others: the constraints of the school, teachers,and students.